2021
DOI: 10.1002/jctb.6617
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide doped hydroxyapatite incorporated photocatalytic membranes for the degradation of chloramphenicol antibiotic in water

Abstract: BACKGROUND In the recent years, photocatalytic membrane process has gained interest in wastewater treatment applications. In this study, the ability of advanced oxidation technology coupled membrane process was evaluated during chloramphenicol (CAP) filtration. Titanium dioxide doped hydroxyapatite (TiO2‐HAP) based photocatalytic membrane for chloramphenicol (CAP) degradation was investigated. The TiO2‐HAP photocatalyst was synthesized by a facile hydrothermal technique and characterized by the transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…The carbonate that occurred in samples probably came from the atmosphere. Further, the OH absorption bends at 1650 cm −1 (δ(OH)) and low-intensity broad bend at 3520 cm −1 (O-H stretching vibrations) suggested that no dehydroxylation had occurred during the formation of the HAp-TiO 2 nanocomposites [26,29]. The dehydroxylation of HAp took place before the decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…The carbonate that occurred in samples probably came from the atmosphere. Further, the OH absorption bends at 1650 cm −1 (δ(OH)) and low-intensity broad bend at 3520 cm −1 (O-H stretching vibrations) suggested that no dehydroxylation had occurred during the formation of the HAp-TiO 2 nanocomposites [26,29]. The dehydroxylation of HAp took place before the decomposition.…”
Section: Resultsmentioning
confidence: 99%
“…37 In addition, the improper disposal of CAP-contaminated wastewater has been identified in water and even drinking water, which certainly causes major health issues in humans and animals. 38 Because of the increasing antibiotic drug pollutants in the global system, many researchers have been very enthusiastic about controlling or monitoring CAP using various analytical methods. In recent years, the conventional analytical techniques for the detection of CAP are high-performance liquid chromatography (HPLC), 39 LCmass spectrometry (LC-MS), 40 gas chromatography (GC), 41 gas chromatography-mass spectrometry, 42 Raman scattering, 43 chemiluminescence, 44 enzyme-linked immunosorbent assay (ELISA), 45 and antibody-based techniques 46,47 are frequently explored for CAP detection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, China, Canada, and the United States monitoring the food safety and control department have set the minimum required performance limit of CAP as 0.3 μg kg –1 . In addition, the improper disposal of CAP-contaminated wastewater has been identified in water and even drinking water, which certainly causes major health issues in humans and animals . Because of the increasing antibiotic drug pollutants in the global system, many researchers have been very enthusiastic about controlling or monitoring CAP using various analytical methods.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of a material surface to act against the attachment of unwanted organisms Ag/ZnO/HA, 117 activated carbon (AC)/HA/polyethersulfone (PES), 118 boron nitrte (BN)/HA, 119 TiO 2 /HA, 120 Ag/nano-TiO 2 , 121 PES/polydopamine/taurine/HA membrane, 122 poly(vinylidene fluoride)(PVDP)/polyvinylpyrrolidone (PVP)/HA membrane, 123 PES/PVP/HA, 124 carbonate apatite/HA/polysulfone (PSF), 125 F/ HA/SiO 2 , 126 dentinal tubules (DTs), 127 zwitterionic polymers 128 and others 127,[129][130][131][132][133]…”
Section: Anti-foulingmentioning
confidence: 99%